Fourier Transform Infrared Spectroscopy vibrational bands study of Spinacia oleracea and Trigonella corniculata under biochar amendment in naturally contaminated soil - Younis, Uzma; Rahi, Ashfaq Ahmad; Danish, Subhan; Ali, Muhammad Arif; Ahmed, Niaz; Datta, Rahul; Fahad, Shah; Holatko, Jiri; Hammerschmiedt, Tereza; Brtnicky, Martin; Zarei, Tayebeh; Baazeem, Alaa; et al. (PloS one, 2021)
Fourier transform infrared spectroscopy (FTIR) spectroscopy detects functional groups such as vibrational bands like N-H, O-H, C-H, C = O (ester, amine, ketone, aldehyde), C = C, C = N (vibrational modes of a tetrapyrrole ring) and simply C = N. The FTIR of these bands is fundamental to the investigation of the effect of biochar (BC) treatment on structural changes in the chlorophyll molecules of both plants that were tested. For this, dried leaf of Spinacia oleracia (spinach) and Trigonella corniculata (fenugreek) were selected for FTIR spectral study of chlorophyll associated functional groups. The study's primary goal was to investigate the silent features of infrared (IR) spectra of dried leave samples. The data obtained from the current study also shows that leaf chlorophyll can mask or suppress other molecules' FITR bands, including proteins. In addition, the C = O bands with Mg and the C9 ketonic group of chlorophyll are observed as peaks at1600 (0%BC), 1650 (3%BC) and 1640, or near to1700 (5%BC) in spinach samples. In fenugreek, additional effects are observed in the FTIR spectra of chlorophyll at the major groups of C = C, C = O and C9 of the ketonic groups, and the vibrational bands are more evident at C-H and N-H of the tetrapyrrole ring. It is concluded that C-N bands are more visible in 5% BC treated spinach and fenugreek than in all other treatments. These types of spectra are useful in detecting changes or visibility of functional groups, which are very helpful in supporting biochemical data such as an increase in protein can be detected by more visibility of C-N bands in FTIR spectra.
Keywords: listy rostlin; Spectroscopy, Fourier Transform Infrared; vibrace; Environmental Pollution; těžké kovy; molekulární struktura; Molecular Structure; Chlorophyll; látky znečišťující půdu; Spinacia oleracea; Absorption, Physicochemical; Trigonella; Soil; Soil Pollutants; Vibration; chlorofyl; Charcoal; Plant Leaves; fyzikální absorpce; Metals, Heavy; půda; znečištění životního prostředí; dřevěné a živočišné uhlí; spektroskopie infračervená s Fourierovou transformací